Avaliação dos pacientes com artrite idiopática juvenil acompanhados no Hospital Universitário Walter Cantídio no período de maio de 2008 a maio de 2012 - Alcântara, Antônia Celia de Castro (2013)
Juvenile idiopathic arthritis (JIA) is the most common chronic disease of childhood in USA and Europe. In Brazil, there are few epidemiological studies on the specific disease. This is the first study in Northeast Brazil who described the clinical profile, response to treatment with biological drugs and non-biological drugs and adverse events in JIA. Exclusion criteria were secondary causes of chronic arthritis. Two reviews with an average interval of 37 months were conducted: the first at baseline, the second at the end, which was researched treatment given, assessment of disease activity through DAS28 (Disease Activity Score), functional assessment by the CHAQ (Childhood Health Assessment Questionnaire) and joint damage by JADI AM (The Modified Juvenile Arthritis Damage Index). Seventy-four patients were enrolled and 05 were excluded because alternative diagnosis of chronic arthritis. We followed sixtynine: 46 girls and 23 boys. Forty-seven (68.1%) came from the capital, 48 (69.5%) lived with both parents. The mean age at onset was 7.89 ± 3.5 years, the average age of definitive diagnosis 9.70 ± 3.9 years and the time interval between the onset of symptoms and definitive diagnosis 12 months (01-60). At the time of definitive diagnosis, the average number of active joints was 7.7. ± 4.7, extra-articular manifestations occurred in 43 (62.3%) and joint deformity in 16 (23%), ESR was elevated in 68 (98.5%).The rheumatoid factor was positive in 16 (23.1%) and the Fan in 08 (11.5%). According to the ILAR classification: 23 (33.3%) had polyarticular negative rheumatoid factor, 13 (18.8%) polyarticular positive rheumatoid factor, 18 (26.0%) as oligoarticular (08 persistent and 10 extended), 10 (14.5%) as systemic, 04 (5.8%) with arthritis associated to enthesitis and 01 (1.4%) as psoriatic arthritis. The deformity group showed greater time interval between onset of symptoms and definitive diagnosis (p=0.04) and more active joints at diagnosis compared to those without deformity (p =0.008). The mean DAS28 at the beginning was 5.42 ± 0.77 and 3.25 ± 1.42 at the end. The mean duration of disease at study was 12.4 ± 6.2 years. In 21.97%, CHAQ was zero. Nineteen (27.5%) patients presented JADI AM> 0. During the study, 50.7% used NSAIDs, 17.3%, intraarticular steroid, 82.6% Methotrexate (MTX), Leflunomide (LFN) 62.3%, 28.9% etanercept, 5.7% adalimumab. MTX monotherapy do not sustained low disease activity in most patients; LFN was a safe and effective therapeutic option to MTX monotherapy before initiating biologic therapy. Etanercept was the most widely used biologic after failure with non-organic. The strategy adopted treatment reduced pain, discomfort, and contributed to improving the quality of life of children.